2018
DOI: 10.21577/0100-4042.20170226
|View full text |Cite
|
Sign up to set email alerts
|

Adenanthera pavonina galactomannan for controlled delivery of rutin – a preliminary study

Abstract: publicado na web em 04/04/2018Improving the development of modified release matrix systems strictly depends on selecting an appropriate agent capable of controlling the drug's release. In this study, Adenanthera pavonina galactomannan was investigated as a potential basis for developing a controlled release of rutin. This galactomannan was extracted, purified and characterized by GPC, NMR and FT-IR spectroscopy. C DEPT 135º NMR and HSQC spectra). The sustained-release tablets containing rutin and galactomannan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated the importance of this biopolymer due to its properties of water solubility and thickener, presenting thus, high versatility of application in several fields (Santos et al, 2015). Many studies using this galactomannan have been exploring the development of new formulations just like edible coatings (Lima et al, 2010), emulsion (Zarnowski et al, 2004;Jaromin et al, 2006), drug delivery (Nobre et al, 2018) and association with other materials, such as hydroxyapatite (Aquino et al, 2017).…”
Section: Phytochemical Analysis Of Seedsmentioning
confidence: 99%
“…Several studies have demonstrated the importance of this biopolymer due to its properties of water solubility and thickener, presenting thus, high versatility of application in several fields (Santos et al, 2015). Many studies using this galactomannan have been exploring the development of new formulations just like edible coatings (Lima et al, 2010), emulsion (Zarnowski et al, 2004;Jaromin et al, 2006), drug delivery (Nobre et al, 2018) and association with other materials, such as hydroxyapatite (Aquino et al, 2017).…”
Section: Phytochemical Analysis Of Seedsmentioning
confidence: 99%